Rasulullah SAW Sebagai Kepala Rumah Tangga - Pribadi, Syofiah; Thohir, Ajid; Hakim, Ajid (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The family is the oldest form of organization in the history of human life. This is evidenced by the existence of a leader in the family named a husband. The absence of a leader, or the inability of a leader to manage an organization will make the organization a mess. The figure of Muhammad SAW as a Prophet and Apostle in the midst of mankind, became the best example of how to become the best leader in the family. Despite being busy as a leader of the people and society, the Prophet sallallahu alaihi wasallam never shirked his obligations in the household. He even often helps his wife, Aisyah, with some work at home. Prophet Muhammad SAW always gave advice to the companions. According to him, a husband should be meek towards his wife and children. Every Muslim should follow the example of the Prophet Muhammad SAW. The purpose of this paper is to describe the special qualities of Prophet Muhammad SAW as the head of the household, Prophet Muhammad as husband and father, as well as how the example of Prophet Muhammad SAW in carrying out the role of the head of the family. The method carried out by the author is a library study. That is a study carried out by searching and reviewing literature or written sources related to the subject matter. As well as seeking and studying from various books and other written sources that have relevance to this discussion. The results of the literature study obtained by Prophet Muhammad SAW personified the role of a perfect husband and father. He was very kind to his wife and children and grandchildren. In worldly affairs, he is very open but serious and dignified when dealing with Allah Almighty. The Prophet played the role of head of household and he did not shirk his obligations as Head of State and leader of the Muslims.